Ecology and conservation of koki (Prosopeia tabuensis) in Tonga : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Ecology at Massey University, Palmerston North, New Zealand - Saafi, Elizabeth Patisepa Kiteau (Massey University, 2002)
The population of Koki Prosopeia tabuensis on 'Eua, Tonga, was studied from August 1999 - November 2000. Line Transect and Point Count methods were used to estimate Koki density and abundance in 'Eua Plantation Forest and analyzed by distance sampling techniques. The density estimates derived by the two methods were compared. Population estimates along six transect lines established in different forest types showed that the Point Count method tended to overestimate Koki density compared with the Line Transect method. Highest Koki density was 0.193 per hectare, and the average density was 0.153 per hectare, suggesting about 1 Koki per 6 hectares in 'Eua Plantation Forest. The 'Eua Plantation forest was divided into four principal forest types and Koki density in each forest types was estimated using the Line Transect and the Point Count methods. Again, the Line Transect method better represented Koki density in these four forest types. Highest Koki density and abundance was associated with Native Forest, closely followed by Pinus caribaea Forest. It is estimated that there were approximately 620 Koki in the 'Eua Plantation Forest in 1999 - 2000. Thirteen other birds were present at the 'Eua Plantation and they did not appear compete with Koki for the same food sources. Koki flying over the 'Eua National Park were calling when flying longer distances. The mean interval between calls for Koki calling while flying was 6.79 (95% C.I = 5.78 - 7.99) seconds. The mean distance travelled by Koki flying and calling over the National Park was 134.50 (95% C.I. = 96.73 - 187.02) meters. Koki fed on a variety of wild fruits and seeds including pinecones and pawpaw. Pinecones appeared to be a major food item in Koki diet at the 'Eua Plantation Forest. Eight Koki nests were found in the year 2000 breeding season. The eight nest trees suffered considerable damage by locals, removing the Koki chicks for sale. The implications of the research findings for future monitoring and conservation of Koki are discussed.
Keywords: Tonga Eua Island; Parrots